Matsushita leadership lessons from the 20th century's most remarkable entrepreneur - Kotter, John P. 1947- (Free Press, 1997)
He was one of the most inspirational role models of all time. Thrown into poverty at age four, Konosuke Matsushita (Mat-SOSH-ta) struggled with the early deaths of family members, an apprenticeship which demanded sixteen-hour days at age nine, all the problems associated with starting a business with neither money nor connections, the death of his only son, the Great Depression, the horror of World War II in Japan, and more. Yet John P. Kotter shows in this fascinating and instructive book how, instead of being ground down by these hardships, Matsushita grew to be a fabulously successful entrepreneur and business leader, the founder of Japan's General Electric: the